A Twin-Herbal Combination was found to have Cardio-Vascular Protection Effects after repeated RCTs on four groups of patients with Different Disease Background A Cross-Biostatical Study - William KF Cheng; Ping Chook; KS Woo; Timothy CY Kwok; Bryan PY Yan; Johnny CM Koon; Ping-Chung Leung (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2021)
Background and Objective: To perform an integrated Cross-Biostatical analysis of four randomized controlled trials (RCTs) to assess the efficacy and safety of oral administration of D&G capsule (D&G) for the maintenance of cardiovascular health. Methods: Data from the populations of four completed RCTs were pooled for this integrated Cross-Biostatical analysis. Mean changes from baseline in IMT and lipid profile were the main lines of attention; treatment differences were compared between D&G and Placebo groups. Primary outcome was Carotid artery intima-media thickness (IMT). Secondary outcome was the lipid profile. Analyses included primary and secondary outcome measures repeated at individual time points.  Results: The pooled RCT data involved 453 subjects (245 D&G; 208 Placebo); demographic characteristics were similar between treatment groups. Taking all 4 groups together, the mean improvements in IMT from baseline to week 24 were 0.9163 to 0.8939 in D&G group, and 0.8997 to 0.8964 in Placebo group. A statistically significant improvement after treatment was observed (P <0.001) in D&G group, not in Placebo group.  Conclusion: The integrated analysis of the pooled biostatic data further confirmed the efficacy and safety of D&G in the vascular protection effects.